Optimization of Glycerin and Sorbitol in Hand Sanitizer Cream with Centella asiatica (L.) Extract - Novela, Yuven; Yuliani, Sri Hartati (Universitas Ahmad Dahlan, 2024)
The use of alcohol-based hand sanitizers can cause dry skin. Centella asiatica (L.) extract can be used as an alternative to alcohol because it contains triterpenoids, especially asiatic acid, potentially an antibacterial and inhibitor of the SARS-CoV-2 virus. Cream is a preparation that can moisturize and protect the skin. Glycerin and sorbitol are humectants often used in cream preparations and have a large percentage in the cream preparation's formula so that they can affect the physical properties of the cream. This study aims to obtain the optimum composition range of glycerin and sorbitol and determine the effect of glycerin and sorbitol as humectants on the physical properties and stability of the hand sanitizer cream with Centella asiatica (L.) extract. The composition optimization was done using a factorial design method on two factors and two levels using the Design Expert 13 (free trial) application. The data on the physical properties and stability of the cream were statistically analyzed using a two-way ANOVA test at a 95% confidence level. The results of qualitative phytochemistry screening showed that the extract contained triterpenoid. The average test of physical properties and stability of physical properties meet the desired criteria: cream type O/W, viscosity 120–170 dPa.s., spreadability of 5-7 cm, shift of spreadability, and shift of viscosity below 10%. The optimum area shows that the formulas F1, FB, and FAB meet the desired criteria.